1990
DOI: 10.1080/00222895.1990.10735527
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Criterion and Feedback Information in Learning a Drawing Task

Abstract: Experiments were designed to examine the influence of criterion and feedback information in the learning of a two-dimensional drawing task. Experiment 1 showed that when the task criterion is well known to the subject, the combined presentation of criterion information and information feedback facilitates the rate of acquisition of the skill but not its overall performance level of achievement. Experiment 2 showed that when the task criterion information is not well known to the subject, presentation of criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
9

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 11 publications
2
27
0
9
Order By: Relevance
“…In studies of limb motor learning, it has been shown that knowledge of performance (KP) feedback has a facilitative effect on learning when the goal of the task is not known (Newell et al, 1990). Otherwise, it has no benefits over and above simple KR feedback (Swinnen et al, 1993, Hodges & Franks, 2001.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of limb motor learning, it has been shown that knowledge of performance (KP) feedback has a facilitative effect on learning when the goal of the task is not known (Newell et al, 1990). Otherwise, it has no benefits over and above simple KR feedback (Swinnen et al, 1993, Hodges & Franks, 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these cautions, few studies have controlled the amount and timing of KP, with KP usually being provided throughout training. Newell et al (1990) compared the effects of KP and KR on healthy adults learning a bimanual coordination task and reported that KP was beneficial when the learners did not know the goal of the coordination task, suggesting that KP aided development of a reliable internal representation of the movement. However, Swinnen et al (1993) reported that when the learning goals are clear to the learner KP gives no benefit over and above simple KR feedback.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In psychomotor learning, coupling kinematic and intrinsic feedback appears to be most beneficial when it supplies information about components of a movement that cannot be measured objectively (33) . This case seems to hold with MR, in which changes in the practitioner's manual input so minute and short-lived as to elude objective measurement often produce significant changes in the client's visible and palpable responses.…”
Section: International Journal Of Therapeutic Massage and Bodywork-vomentioning
confidence: 99%
“…it provides specific qualitative information about the movement that occurred) 15 . Previous research has indicated that detailed knowledge of performance feedback can facilitate acquisition of a novel motor routine 16 . Ultrasound has several advantages over other technologies used to visualize speech.…”
Section: Introductionmentioning
confidence: 99%